A river runs through it: Land-use and the composition of vegetation along a riparian corridor in the Cape Floristic Region, South Africa - Meek, C.; Richardson, D.; Mucina, Ladislav (2010)
Riparian zones are important for the many ecosystem services they supply. In settled areas, the vegetation of such zones is shaped by human land-use; this often creates conditions under which alien plant species thrive. Alien plants have been shown to induce large-scale changes in riparian habitats, and they pose a major threat to the continued provision of key ecosystem services. We used direct gradient analysis to assess correlations between land-use and the composition of vegetation along a riparian river corridor in the highly transformed landscape surrounding Stellenbosch in South Africa’s Western Cape Province. Vegetation plots were sampled along the entire length of the river from headwaters to estuary (ca. 40 km). Plant community composition was analyzed in relation to land-use data collected in the field, and additional land-use variables computed from digital land-cover data. Patterns of plant community structure were found to be directly related to land-use, with measures of cover, richness, and diversity differing significantly among land-use types. Portions of the riparian zone adjacent to agricultural land had the greatest level of alien plant cover, while areas bordered by urban land maintained the highest alien species richness. Areas adjacent to grazing and natural lands showed intermediate and low levels of invasion, respectively. Several native species were found to persist in areas with high abundance and diversity of invasive alien plants, suggesting that they will be valuable focal species for future restoration attempts. Due to the level of human-mediated change in many areas of the riparian zone, restoration to historic conditions over most of the river is not considered feasible. These areas should be recognized as examples of novel ecosystems, and management efforts should focus on restoring or creating desirable ecosystem functions, rather than on achieving assemblages comprising only native species.